PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION - Nur Hafizah (Jurnal Edukasi dan Penelitian Matematika, 2018)
The Ability of understanding mathematical concepts is basic ability that must had students in learning mathematics. In this research, to improve the ability of understanding of mathematical concepts applied cooperative learning model of Student Teams Achievement Division (STAD). This research type is quasi experiment with static group design. The population of research is class VIII SMPN 18 Padang academic year 2017/2018. Sampling was randomly selected and VIII3 was selected as experimental class and class VIII4 as control class. The instrument of this research is a quiz and a final test of understanding of mathematical concepts. Quiz results are used to see the average increase in the quiz value of each meeting. The final test results are used to compare the understanding of the mathematical concepts of students who are learning by using STAD with an understanding of the mathematical concepts of students learning by using conventional learning. The quiz give results that there is a significant increase in the mean value of each meeting quiz. The final test gives the result that the student’s understanding of mathematical concepts that learn to use STAD type of cooperative learning model is better than the understanding of mathematical concepts that students learn to use conventional learning at grade VIII SMPN 18Padang.Keywords – understanding of mathematical concepts, student teams achievement division